Effect of mother's knowledge on posteducation toward rehospitalization of young children with pneumonia† - Casman Casman; Nurhaeni Nani; Waluyanti Fajar Tri (Sciendo, 2022)
The rehospitalization rate of children <5 years old with pneumonia is still high. The risk of hospitalization becomes higher in mothers with low knowledge of their child's disease. The purpose of this study was to determine the effect of post-health-education maternal knowledge in cases of rehospitalization and to determine the differences in rehospitalization rate based on the type of health education media.